Dynamical Evolution of Sub-km Sized Main-belt Asteroids with Involving Thermal Radiation Effects - Budi Dermawan; A. Fermita (Institut Teknologi Bandung, 2011)
Inconsistencies between asteroid’s evolutionary model and observational results have been convincingly explained by thermal radiation effects that cause asteroids to experience orbital drifts. To investigate influences of the effects, we conducted 10 million yr orbital integration of hypothetical sub-km sized Main-belt asteroids. Numerical integration was run to propagate orbital dynamics of the asteroids by taking into account typical physical parameters of regolith- and basaltic-type surfaces of asteroids. Delivery processes from the Main-belt asteroids to near-Earth space are occurred by the aids of planetary orbital resonances and gravitational perturbations. In general, we find that thermal radiation effects play as an important role in the early evolution (< 1 million yr), which guide the asteroids to follow different evolutionary paths than those of without involving the effects. This study indicates that asteroids whose surface belongs to basaltic-type have higher orbital mobility.